THE RELATIONSHIP BETWEEN CONFORMITY AND IMPULSIVE BUYING IN ADOLESCENTS IN MAKASSAR CITY - Muhammad Rhesa; Ichsan Ichsan; Muhammad Reza Firmansyah (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2023)
Teenagers are known as trendsetters who can quickly follow the latest trends and become a very easily influenced group. Teenagers often purchase attractive products impulsively and only follow their peers in their group and environment. Impulsive buying is the emergence of a sudden urge and a solid feeling to buy without any pre-planned purchases. This study aims to determine the relationship between conformity and impulsive buying among adolescents in Makassar City. The hypothesis in this study is that there is a relationship between unity and impulsive buying among adolescents in Makassar City. The results showed a significance value of 0.049 and a correlation coefficient of 0.198, which means there is a weak and positive relationship between conformity and impulsive buying among adolescents in Makassar City. This research was conducted on 100 young girls and boys aged 13-18 with a peer group and teenagers living in Makassar City.